Carbon-Based Adsorbents from Biochar and Microcrystalline Cellulose for Phenol Removal in Aqueous Solutions - Juleanti, Novie; Fitri, Erni Salasia; Siregar, Patimah Mega Syah Bahar Nur (Indonesian Journal of Material Research, 2024)
This study investigates the adsorption characteristics of phenol on rice husk biochar (BC) and microcrystalline cellulose (MC), with a focus on their structural, kinetic, isotherm, and thermodynamic properties. XRD and FTIR analyses reveal that BC and MC possess similar carbon-based structures. Nitrogen adsorption-desorption isotherms highlight BC’s higher surface area and pore volume, which likely contribute to its superior adsorption performance. Adsorption kinetics are best described by the PSO model, indicating chemisorption as the rate-limiting step. Isotherm studies show that the Langmuir model provides a better fit, suggesting monolayer adsorption on homogeneous surfaces. Thermodynamic parameters indicate that phenol adsorption onto BC is endothermic and spontaneous, with adsorption capacity increasing with temperature, while MC shows minimal temperature sensitivity. The adsorption capacity of phenol using BC and MC was obtained as 28.50 mg/g and 13.25 mg/g, respectively. The reusability tests reveal that BC retains significant adsorption capacity over multiple cycles compared to MC. Overall, BC is identified as a more efficient and reusable adsorbent for phenol removal in aqueous solutions.